Studies on the Water Stable Aggregates of Some Murshidabad Soils (W. Bengal) - Chakrabarti, D.C.; Das, S.C. (Journal of Soil and Water Conservation, 2022)
Soil structure is commonly defined as the arrangement of soil particles. The stability of structure resides in the aggregates. Hence the stability of soil aggregates in water is an index of the stability of soil structure. This is also an important physical property of the soil that affects infiltration, permeability and reten-tivity of soil moisture—thus helps in the conservation of soil and water. The present investigation was undertaken to study the distribution of water stable aggregates in some soils of Murshidabad districts in West Bengal.